Politisasi Ayat-Ayat Al-Qur’an (Kajian Term Amin dalam Al-Qur’an dan Relevansinya terhadap Konteks Pemilihan Presiden dan Wakil Presiden 2024) - Firnanda Anggraeni Maghfiroh; M. Mukhid Mashuri; Wiwin Ainis Rohtih (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This article aims to analyze the term Amin in the Qur'an and its relevance to the election of the President and Vice President of the Republic of Indonesia in 2024. This is motivated by the fact that based on the campaign for the election of President and Vice President number 01, Dadang Muliawan as a volunteer campaigned by obliging the victory of Anis Baswedan-Muhaimin Iskandar and exposing his defeat. In his campaign, he strengthened his argument by mentioning a dozen verses of the Qur'an containing the term Amin. By using qualitative research methods with library research and descriptive-analytical data analysis, the results show that the verses that mention the word Amin in 14 verses in the Qur'an textually do not support that the pair Anies Baswedan and Muhaimin Iskandar are then abbreviated as